Less Frequent Sequence Mismatches in Variants of Concern (VOCs) of SARS-CoV-2 in the Real-Time RT-PCR Assays Developed by the National Institute of Infectious Diseases, Japan - Shirato, Kazuya; Matsuyama, Shutoku; Takeda, Makoto (Japanese Journal of Infectious Diseases, 2022)
Various variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began emerging worldwide from the end of 2020 to the beginning of 2021. The variants GRY/VOC202012/01 (B1.1.7), GH/N501Y.V2 (B1.351), and GR/N501Y.V3 (P1) are characterized by N to Y amino acid substitution at position 501 in the S protein. The variant containing L to R substitution at position 452 in the S protein G/L452R.V3 (B1.617) was endemic to India. The heightened concern regarding these variants is related to their increased viral infectivity. Information about nucleotide mismatch(es) on the primer/probe sequence is important for maintaining good performance of real-time PCR assays. In this study, real-time RT-PCR assays developed by the National Institute of Infectious Diseases, Japan (NIID-N2 and NIID-S2 assays), were reviewed to analyze nucleotide mismatches of variants in primer/probe sequences. The frequency of mismatched sequences in three variants (GRY/VOC202012/01, GH/N501Y.V2, and GR/N501Y.V3) was lower than that in all SARS-CoV-2 sequences. The mismatch, that G to C substitution at nucleotide 8 in reverse primer of S2 set, elevated to about 16.3% in G/L452R.V3, however the substitution did not affect the analytical sensitivity of assay. Therefore, the study indicates that the NIID-N2 and NIID-S2 sets detect VOCs of SARS-CoV-2 with reliable efficiency.